2015
DOI: 10.1128/aac.04957-14
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Pharmacokinetic Application of a High-Performance Liquid Chromatographic Technique for Determining the Concentrations of Amodiaquine and Its Metabolite in Plasma of Patients Treated with Oral Fixed-Dose Amodiaquine-Artesunate Combination in Areas of Malaria Endemicity

Abstract: dArtemisinin-based combination therapies (ACTs) have been adopted by most African countries, including Nigeria, as first-line treatments for uncomplicated falciparum malaria. Fixed-dose combinations of these ACTs, amodiaquine-artesunate (FDC AQAS) and artemether-lumefantrine (AL), were introduced in Nigeria to improve compliance and achieve positive outcomes of malaria treatment. In order to achieve clinical success with AQAS, we developed and validated a simple and sensitive high-performance liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The plasma concentration‐time profiles of AQ and DEAQ in all the arms of this study are as shown in Figures and , respectively, whereas the derived pharmacokinetic parameters for AQ and DEAQ are as shown in Tables and , respectively. In this study, as it had been reported in previous human studies involving the administration of a single dose of AQ, there was rapid absorption and an extensive metabolism of AQ to its pharmacologically active derivative, DEAQ, which is thought to be responsible for most of the therapeutic effect of the drug . In fact, AQ was cleared from the system within 30 minutes and it has been rightly suggested that DEAQ should be monitored in vivo during malaria therapy instead of AQ.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The plasma concentration‐time profiles of AQ and DEAQ in all the arms of this study are as shown in Figures and , respectively, whereas the derived pharmacokinetic parameters for AQ and DEAQ are as shown in Tables and , respectively. In this study, as it had been reported in previous human studies involving the administration of a single dose of AQ, there was rapid absorption and an extensive metabolism of AQ to its pharmacologically active derivative, DEAQ, which is thought to be responsible for most of the therapeutic effect of the drug . In fact, AQ was cleared from the system within 30 minutes and it has been rightly suggested that DEAQ should be monitored in vivo during malaria therapy instead of AQ.…”
Section: Resultsmentioning
confidence: 58%
“…Blood samples were collected before dosing and at 0.25, 0.5, 1, 2, 4, 8, 12 and 24 hours into heparinized tubes and immediately centrifuged at 4000 rpm (2147 g ) for 10 minutes to obtain plasma which were stored at −20°C until analysis. Plasma concentrations of amodiaquine (AQ) and desethylamodiaquine (DEAQ) were simultaneously determined using a modified validated HPLC method . For sample preparation, 10 μL of a 1 ng/mL hydroxychloroquine (HCQ) solution was added to 500 μL of plasma in an extraction tube and made up to 2 mL with distilled water and vortex‐mixed for 1 minute.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were analyzed for ADQ and DEAQ using the HPLC method reported by Adedeji et al 24 Sample extraction involved precipitation of the plasma proteins, followed by extraction as follows: in a 15 mL extraction tube, 1 mL of plasma, 1 mL of acetonitrile and 2 µL of 50 µg/mL of hydroxychloroquine (internal standard) were added and centrifuged for 20 min at 3,000 ×g to precipitate the plasma protein. The supernatant was then separated into clean and dry extraction tubes, to which 2 mL of diethyl ether was added.…”
Section: Drug Analysismentioning
confidence: 99%
“…The calibration procedures were as reported. 24 A calibration curve, based on peak area ratio, was prepared by spiking drug-free plasma with standard solutions of ADQ and DEAQ to give concentration ranges of 100-1,000 ng/mL for both ADQ and DEAQ. The samples were taken through the extraction procedure described above.…”
Section: Drug Analysismentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] However, last few decades witnessed an upsurge in electrochemical methods for the detection and determination of these compounds. Therapeutic drug monitoring (TDM) is a clinical strategy that measures drug concentration in a patient's bloodstream to monitor its compliance, efficacy and toxicity, thus optimizing and managing individual medication regimen.…”
Section: Introductionmentioning
confidence: 99%